Streptomyces cahuitamycinicus sp. nov., Isolated From Desert Soil and Reclassification of Streptomyces galilaeus as a Later Heterotypic Synonym of Streptomyces bobili - Saygin, Hayrettin; Ay, Hilal; Guven, Kiymet; Cetin, Demet; Sahin, Nevzat (Microbiology Soc, 2020)
A novel actinobacterial strain, designated 13K301(T), was isolated from a soil sample collected from the Karakum Desert, Turkmenistan. The taxonomic position of strain 13K301(T) was revealed by using a polyphasic approach. On the basis of 165 rRNA gene sequence analysis, strain 13K301(T) belongs to the genus Streptomyces and had highest sequence similarity to 'Streptomyces qaidamensis' S10(T) (99.2 %), Streptomyces flavovariabilis NRRL B-16367(T) (98.9 %) and Streptomyces phaeoluteigriseus DSM 41896(T) (98.8 %), but the strain formed a distinct Glade in the phylogenetic tree. The DNA-DNA relatedness and average nucleotide identity values as well as evolutionary distances based on multilocus (atpD, gyrB, recA, rpoB and trpB) sequences between strain 13K301(T) and closely related type strains were significantly lower than the recommended threshold values. The cell wall contained LL-diaminopimelic acid and the whole-cell hydrolysates were glucose and ribose. Diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol were determined as the predominant polar lipids. The major menaquinones were identified as MK-9(H-8) and MK-9(H-6). On the basis of these genotypic and phenotypic data, it is proposed that strain 13K301(T) should be classified as representative of a novel species of the genus Streptomyces, for which the name Streptomyces cahuitamycinicus sp. nov. is proposed. The type strain is 13K301(T) (=DSM 106873(T) =KCTC 49110(T)). In addition, the whole genome-based comparisons as well as the multilocus sequence analysis revealed that the type strains of Streptomyces galilaeus and Streptomyces bobili belong to a single species. It is, therefore, proposed that S. galilaeus be recognised as a heterotypic synonym of S. bobili for which an emended description is given.
Saygin, Hayrettin/0000-0002-8642-5872; Guven, Kiymet/0000-0001-6683-0419; Ay, Hilal/0000-0002-8735-4703; Cetin, Demet/0000-0003-1186-4229; Sahin, Nevzat/0000-0002-6026-656X
Keywords: Actinobacteria; Phylogenomic; Streptomyces; Karakum Desert